Covid-19 Vaccine Or Negative Test For Covid-19: A Glimpse Into The Future - Ahmad Mahfuz, Gazali (https://codeblue.galencentre.org/malaysia/, 2021)
Our road to recovery from the pandemic is far from over, but we must be optimistic that thingscan go back to normal.